Anorectal malformation with apple peel atresia: case report of a rare association - Kamble, Archana M.; Saoji, Rajendra (International Surgery Journal, 2018)
Anorectal malformations (ARM) are common congenital malformations. They are mostly associated with other congenital anomalies including but not limited to vertebral anomalies, cardiac malformations, Tracheoesophageal fistula, esophageal atresia, Renal anomalies, limb anomalies and aneuploidy (Trisomy 21). Apple-peel atresia or ‘Christmas-tree deformity’ consists of a high jejunal atresia with discontinuity of the small bowel and a wide gap in the mesentery. Association of Apple peel atresia with ARM has been reported by many authors in past and in any neonate presenting with ARM proximal atresia needs to be ruled out before surgical intervention is undertaken and newborns with ARM and presenting with drooling of saliva, bilious or non-bilious vomiting in presence of non-distended abdomen must give rise to a suspicion of associated atresia. We are reporting this case of high anal atresia with apple peel atresia of terminal ileum who was treated by double barrel ileostom to emphasize the importance of knowing this association.